Bactericidal Activity, Isolation and Identification of Most Active Compound from 20 Plants used in Traditional Mexican Medicine Against Multidrug-Resistant Bacteria - García Her, D.G.; Rivas Morales, Catalina; Rivas Galindo, Verónica Mayela; Rodríguez, J.; Galindo Rodríguez, Sergio Arturo; Leos Rivas, Catalina (2018)
Abstract Background and Objective: Plants are used in Mexico as traditional medicine for the treatment of diverse illnesses such as stomach pain, fever, diarrhea, insomnia, flu and other respiratory diseases. Twenty were selected to determine their bactericidal activity. The aim of this study was the isolation of molecules from plants used in Mexican traditional medicine. Materials and Methods: Using chromatographic procedures, the responsible bactericidal molecules from rosemary was extracted and then identified by spectroscopic analysis IR, 1H NMR, 13C NMR, DEPT, HSQC and GC-MS. Measures of central tendency were determined by statistical analysis. Results: Ten of these plants showed bactericidal activity against multidrug-resistant bacteria. This biological activity was reported for Carya illinoensis against Pseudomonas aeruginosa , also for Equisetum robustum , Stevia rebaudiana and Castela texana against Methicillin resistant Staphylococcus aureus (MRSA). The methanolic extract of Rosmarinus officinalis (rosemary) showed important bactericidal activity against MRSA (ATCC BAA-44) and clinically isolated MRSA. Conclusion: Rosemary’s bactericidal molecules were isolated and then identified as a mixture of betulinic, oleanolic and ursolic acid (MIC = 725 µg mLG1). Key words: Rosmarinus officinalis , multidrug-resistance, MRSA, thin layer chromatography, flash chromatography, 1H NMR, 13C NMR, triterpenic acids